La contradicción y su aplicación en contravenciones de violencia contra la mujer o miembros del núcleo familiar. - Andrade, Elvia E. (2021)
The research work with the theme "Contradiction and its application in contraventions of violence against women and members of the family nucleus" is a study of contradiction as a guarantee that reaches its expression in the oral trial stage, as evidence practice; the general objective was to analyze contradiction and its application in contraventions of violence against women or members of the family nucleus. A qualitative methodology and descriptive research approach was used for the development of the study. A semi-structured interview containing eight (8) questions was applied to eight (8) participants: two (2) judges of violence against women or family members, three (3) public defenders and three (3) lawyers in free practice. The findings of the opinions expressed allowed us to conclude with the identification of the theoretical elements of the right to defense in the guarantee of contradiction, it was determined that the evidence within the oral trial hearing in cases of contraventions against Violence against Women or Family Members, violates the rights to due process and defense; Therefore, it is recommended to train the experts in the efficient execution of their responsibilities at the moment of assuming the representation of expertise; and thus trust in their technical and operative capacity to carry out the expertise, in order to avoid incurring in a judicial error and to guarantee the constitutional principles of an effective tutelage and the right to defense.